Electronic database protection and the limits of copyright : what options for developing countries? - Oriola, Taiwo A. (2004)
Focuses on electronic database protection and the limitations confronted by copyright. Looks at the form of protection developing countries might wish to adopt. Examines Nigeria's copyright law..